Assessment of morbidity and mortality by influenza A (H1N1) among pregnant women in Western Rajasthan, India (International Journal of Scientific Research and Management (IJSRM), 2017)
Background: Influenza has a major impact on public heath, First outbreak of influenza as a pandemic declared by WHO in June 2009. The present study determines the morbidity and mortality of influenza A (H1N1) by real time reverse transcriptase polymerase chain reaction (RT-PCR) method in pregnant women. Objective: To study the morbidity and mortality of influenza A (H1N1) by RT-PCR Method in pregnant women. Materials and Methods: 702 respiratory samples (nasopharyngeal swabs) of reproductive age group (17 to 45 yrs) women were collected from Dr S. N. Medical College & associated group of Hospitals from January 2015 to March 2015. The samples were collected and processed as per World Health Organization (WHO) guidelines. Viral RNA was extracted and one-step RT-PCR was performed to detect influenza A (H1 and N1) virus. Results: Out of 702 samples 230 (32.7%) were pregnant and 472 (67.3%) were non pregnant women. Among pregnant 63 (27.4%) and among non pregnant 120 (25.4%) were positive for influenza A (H1N1) and 18 (28.5%) pregnant women died due to influenza A (H1N1) infections. Conclusion: It was observed that influenza A (H1N1) was prevalent in pregnant women in western Rajasthan (Jodhpur). We emphasize on early detection and monitoring of influenza in pregnant women which will be helpful in patient management who are at risk for influenza complications.